(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article is devoted to the analysis of ethnic teams that moved to Movaraunnahr and Khorezm areas in the XIII-XV centuries, to the analysis of the ethnames in these areas. The article shows the impact of the Mongolian talent to the local population of Movarunnahr to ethnic and some ethnos in this place.